The Role of Job Satisfaction and Employee Engagement in Talent Management - D. B. Zhulamanova; G. K. Niyetalina (Экономика: стратегия и практика, 2023)
Talent management is important for organizations, first of all, to gain a competitive advantage. Thehigh demand for talent imposes special requirements on employers at the global and state levels. The identification of factors contributing to the retention of talents within the management process, and testing of the formed model, was designated as the main purpose of the article. The study identified independent variables, such as job satisfaction and engagement to work, and examined how they contribute to the dependent variable, i.e. talent retention. Smart PLS4 and IBM SPSS programs for statistical data processing were used to assess the quality of the model and conduct multi-regression analysis. During the analysis, the task was set to take into account the aspect of differences and gender diversity between age generations, which can influence variables. To perform this task, a significance test was conducted, that is, Anova and Manova analysis of variance. As a result of an online survey of 126 respondents, primary data were obtained. Based on the confirmation and non-confirmation of hypotheses, a number of conclusions have been made. Factors such as engagement and job satisfaction showed a high level of influence on the retention of the necessary personnel in the workplace (70.7%). In order to minimize the shortage and turnover of labor in the labor market, it is necessary to pay attention to an inclusive approach, as it helps to prevent the outflow of talent.